PENYIMPANGAN PRAGMATIK PADA DIALOG DALAM NOVEL SAGA NO GABAI BACCHAN (Universitas Negeri Jakarta, 2015)
Pragmatics can be divided into two terms, (1) pragmatic as something is taught, (2) pragmatic as a coloring in teaching action. The first part is subdivided into two things, (a) the linguistic pragmatics as a field of study, and (b) pragmatic as one face in language or the so-called communicative function. Therefore, pragmatics relate to the conditions which resulted in a matching or absence of language in communication. The dialogues in the novel Saga no Gabbai Bacchan can be identified by the pragmatic aspects. The message conveyed otherwise in accordance with the conditions will lead to a different interpretation. This will lead to deviations pragmatic. The message conveyed otherwise in accordance with the conditions will lead to a different interpretation. This will lead to deviations pragmatic. Pragmatic deviation is a deviation that occurs due to irregularities in the communicative situation with the disclosure of the message to the recipient differently interpreted. This is because of differences in understanding in understanding the message delivered by messenger.